2003
DOI: 10.1117/12.501007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular contrast in optical coherence tomography using a pump-probe technique and a optical switch suppression technique

Abstract: Molecular contrast in optical coherence tomography using a pump-probe technique and a optical switch suppression technique," Proc. SPIE 5140, Optical Coherence Tomography and Coherence Techniques, (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Unlike the latter, the new optical switch suppression technique detects the conformational change of molecules before and after the pump suppression. There are only two types of pump suppression OCT contrast agents reported so far, which are bacteriorhodopsin (bR) [ 54 ] and phytochrome A [ 55 ]. Such kinds of molecules can reversibly change from one stable state to another through pump excitations.…”
Section: Pump Suppression Oct and Its Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the latter, the new optical switch suppression technique detects the conformational change of molecules before and after the pump suppression. There are only two types of pump suppression OCT contrast agents reported so far, which are bacteriorhodopsin (bR) [ 54 ] and phytochrome A [ 55 ]. Such kinds of molecules can reversibly change from one stable state to another through pump excitations.…”
Section: Pump Suppression Oct and Its Applicationsmentioning
confidence: 99%
“…Therefore, an OCT probe can scan at different stages to calculate the 3D distribution of molecular contrast agents. Yang et al, presented a pump suppression OCT system and demonstrated clear signals from bR solution samples during the scan [ 54 ]. In the original state, bR has an absorption peak in the javascript:void(0)red-green region of the spectrum.…”
Section: Pump Suppression Oct and Its Applicationsmentioning
confidence: 99%